2018
DOI: 10.1037/edu0000235
|View full text |Cite
|
Sign up to set email alerts
|

Different presentations of a mathematical concept can support learning in complementary ways.

Abstract: Previous research has found that different presentations of the same concept can result in different patterns of transfer to isomorphic instances of that concept. Much of this work has framed these effects in terms of advantages and disadvantages of concreteness or abstractness. We note that mathematics is a richly structured field, with deeply interconnected concepts and many distinct aspects of understanding of each concept, and we discuss difficulties with the idea that differences among presentations can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…The result was consistent with some previously reported works, who argued that higher prior knowledge, comprehensive learning approach, problem-based teaching, and higher assessment impact scores predict higher basic-learning skill scores (Baumert et al, 2017a;Fries et al, 2019;Gearing & Hart, 2019;Gersten et al, 2009;Hakyolu & Ogan-Bekiroglu, 2016;Han et al, 2015;C. H. Hill et al, 2015;Kilion, 2016;Lampinen & McClelland, 2018;Linsell et al, 2012;Nguyen, 2016;Rimbey, 2013;Santagata & Yeh, 2014). In conclusion, H # 5: The higher prior knowledge, comprehensive learning approach, problem-based teaching, and higher assessment impact scores predict higher basic-learning skill scores, is been supported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result was consistent with some previously reported works, who argued that higher prior knowledge, comprehensive learning approach, problem-based teaching, and higher assessment impact scores predict higher basic-learning skill scores (Baumert et al, 2017a;Fries et al, 2019;Gearing & Hart, 2019;Gersten et al, 2009;Hakyolu & Ogan-Bekiroglu, 2016;Han et al, 2015;C. H. Hill et al, 2015;Kilion, 2016;Lampinen & McClelland, 2018;Linsell et al, 2012;Nguyen, 2016;Rimbey, 2013;Santagata & Yeh, 2014). In conclusion, H # 5: The higher prior knowledge, comprehensive learning approach, problem-based teaching, and higher assessment impact scores predict higher basic-learning skill scores, is been supported.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it is evidenced that approaches to instruction and curriculum design, formative assessment data, feedback to students, prior knowledge, pedagogical knowledge, individual learning support, teachers' mathematical knowledge, problem-based lessons, on-going professional development for teachers impact student's basic-learning skill in mathematics. Garet et al (2016) revealed that math content knowledge and instructional practice were generally not correlated with student math achievement, but Lampinen and McClelland (2018) pointed out that pedagogical materials affect learning. Project-based learning instruction, as well as diagnostic assessment information, influenced student achievement in mathematics Han, Capraro, and Capraro (2015); Linsell et al (2012).…”
Section: Relationship Between Prior Knowledge Comprehensive Learningmentioning
confidence: 99%
“…If the different levels of abstraction share structural features, sharing computation should improve generalization. Homoiconicity could also support the ability to build abstractions recursively on top of prior abstractions, as humans do in mathematical cognition (15)(16)(17). Although homoiconicity is not a necessary part of metamapping, we suggest that homoiconic approaches will be beneficial and verify this empirically, see Polynomials section).…”
Section: Model Architecture and Training Methodsmentioning
confidence: 70%
“…External representations can support and constrain but may also hinder learning and reasoning in characteristic ways. That is, different external representations or combinations thereof affect what is processed and encoded (Knuuttila 2011;Lampinen and McClelland 2018;Louca and Zacharia 2012). For example, the use of graphs instead of tables leads to more flexible performance when interpreting data, but graphs can also induce interpretive bias (Braithwaite and Goldstone 2013).…”
Section: Multiple External Representationsmentioning
confidence: 99%
“…Second, MERs can constrain interpretation by virtue of familiarity or their inherent properties. For example, Lampinen and McClelland (2018) argue that different representations Fig. 1 The different functions of MER as conceptualized in the DeFT framework by Ainsworth (2006) support the learning of complementary aspects of a target system (e.g., a scientific principle or a theory) by triggering different reasoning systems.…”
Section: Multiple External Representationsmentioning
confidence: 99%